PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS MCDONALD'S SUNTER BARAT) - Ardiyana, Friska; Nurseno, Bertadi (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The purpose of this study is to determine how the effect of independent variables, namely Product Quality, Price, and Promotion on the dependent variable, namely Purchase Decision. The object of research used in this study is McDonald's Sunter Barat consumers. This research is a quantitative research. The sample in this study amounted to 97 respondents taken using accidental sampling techniques. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis used is multiple linear regression analysis, t test, F test, and determinant coefficient. Data processing tools used in this study SPSS program version 26. The results in this study show that based on the t test obtained the variables Product Quality, Price and Promotion partially have a positive and significant effect on Purchase Decision. Similarly, simultaneously the variables of Product Quality, Price, and Promotion have a positive and significant effect on Purchase Decision at McDonald's Sunter Barat.